Determining the level of sexually transmitted diseases (STDs) awareness in Ota, Nigeria. - Bishop, Sheila A.; Okagbue, Hilary I.; Adoghe, Victor O. (Journal of Public Health: From Theory to Practice (2198-1833), 2021)
Aim: The aim of this research is to determine the level and factors that contribute to the awareness of sexually transmitted diseases in Ota in the Ado/Odo local government area of Ogun State, Nigeria. Subjects and methods: A questionnaire designed to suit the demographic was administered to selected residents of Ota, Ogun State, Nigeria. The subjects were mainly adolescents, and purposive sampling was adopted. Chi-square test of association was used to establish relationships between the various sociodemographic and awareness variables. Results: The results showed the following: a) in general, the awareness level of STDs is moderate, b) there is widespread misconception about STDs, c) Age is significantly associated with parental counselling (p = 0.019), friends and relatives (p = 0.023), religious counselling (p = 0.026) and NGOs (p = 0.001), d) gender is significantly associated with parental counselling (p = 0.05), NGOs (p = 0.012), and medical consultation (p = 0.008), e) educational background is significantly associated with medical consultation (p = 0.019), and f) religion is a predictor of general knowledge about and preventive measures for STDs, at a 0.05 level of significance. Conclusion: There is low awareness of the non-risk factors, and moderate awareness concerning general knowledge, mode of transmission, and preventive measures against STDs. A high level of awareness is recommended if reduction of the prevalence of STDs is to be achieved. Parental, religious, and NGO counselling is strongly recommended. Religious organisations have to be fully engaged in order to reduce the spread of STDs.